Positive correlation of serum interleukin-13 and total immunoglobulin E in bronchial asthma patients - Javaid, Khursheed; Nadeem, Ahmad; Adhami, Saleem u Zaman; Hussain, Malik Asif; Tahir, Romeeza; Shahzad, Faheem; Jahan, Shah; Afzal , Nadeem (Bangladesh Journal of Medical Science, 2022)
Background: Asthma is a chronic inflammation of airways, associated with hyper-responsiveness of the bronchial tree, resulting in reiterated attacks of cough, wheezing, chest tightness, and breathlessness. Aapproximately 4 Pakistani adults out of 100 persons have been reported to suffer from asthma in year 2002-03.This study focuses on determining interleukin-13 (IL-13) and immunoglobulin E (IgE) in asthma patients and healthy subjects. Settings and Design: Methods and Material: The study assessed the level and correlation of IL-13 and IgE in bronchial asthma patients. Fifty bronchial asthma patients with allergy history and thirty healthy individuals were included. The patients were selected from Gulab Devi Chest Hospital, Lahore, Pakistan. Total serum IgE and IL-13 were determined by ELISA technique.SPSS (Version 20.0) software was used for statistical analysis. Kolmogorov-Smirnov, Shapiro-Wilk test, Student t-test and Mann-Whitney test have been used in analysis. Results: The mean (±SD) values of IL-13 concentration (pg/ml) in asthmatics and controls (healthy) were 1574 (± 409) and 390 (± 23). Moreover, median (IQR) value for both groups were 1415.8 (1398-1554) and 394.3 (384.3- 404.3), respectively. Conclusions: To sum up, we have found that bronchial asthma patients had significantly increased level of total serum IgE and IL-13 and we found a positive correlation between these parameters. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 596-600